Export Promotion Agencies Revisited - Lederman, Daniel; Olarreaga, Marcelo; Payton, Lucy (2012)
The number of national export promotion agencies has tripled over the past two decades. Although more countries made them part of their export strategy, studies criticized their efficacy in developing countries. The agencies were retooled, partly in response to these critiques. This paper studies the impact of today's export promotion agencies and their strategies, based on new survey data covering 103 developing and developed countries. The results suggest that on average they have a statistically significant effect on exports. The identification strategies highlight the importance of EPA services for overcoming foreign trade barriers and solving asymmetric information problems associated with exports of heterogeneous goods. There are also strong diminishing returns, suggesting that as far as export promotion agencies are concerned, small is beautiful.